The Role of Problem-Based Learning Model in Optimizing Senior High School Students' Critical Thinking Skills in Biodiversity Material: A Literature Review - Renny Threesje Tumober; Albert Lumbu; Semuel Jeujanan; Rudolf Doni Abrauw (Postgraduate, University of Mataram, 2025)
Through PBL, students do not only memorize facts, but are invited to analyze real problems related to biodiversity, such as species extinction or ecosystem damage. This approach encourages students to find solutions, gather information from various sources, and develop logical arguments, which are the core of critical thinking. Thus, PBL effectively transforms passive learning into active learning, equipping students with essential skills to understand and contribute to global environmental issues. This research aims to analyze and explain the concept and characteristics of the Problem-Based Learning (PBL) Model; the relationship between PBL and critical thinking skills; identify the benefits and challenges of implementing PBL; and explain the implementation of PBL in biodiversity material. The objectives are to identify what is known, find research gaps, and provide a basis for further research. The results of this study are Problem-Based Learning (PBL) is an educational model that makes authentic problems the main foundation in the student learning process; PBL is student-centered, utilizing real problems to trigger independent investigation and group collaboration. This model aims to develop problem-solving and self-reflection skills. General stages of PBL include: Problem orientation: Introducing the problem to students; Student organization: Forming study groups; Guiding inquiry: Facilitating the search for solutions; Development and presentation of results: Presenting findings. • Process analysis and evaluation: Reflecting on learning; PBL is highly effective in improving students' critical thinking skills.